Pengaruh Kreativitas Siswa Dalam Model Pembelajaran Problem Based Learning Kelas IV - Rizki Zuliani; Nasya Uriani Fugri; Arza Amelia Perdana (CV. ITTC INDONESIA, 2023)
Education has an important role in creating quality human resources. Efforts to improve human quality are aimed at creating national cadres who will carry out development in the future. It is through education that the quality of human resources can be improved. The role of the teacher is very important because it is the teacher who deals directly with students as future cadres of the nation. So it is required that there is an education system and appropriate learning model in teaching and learning activities for each subject so as to create an effective, efficient and attractive learning situation for every student to always be active in the learning process.Identification of the problem in this study is how to increase the creativity of fourth grade students at SDN Poris Pelawad 6 in the 2022/2023 academic year by using problem-based learning. The background of the problem above, the research problem formulated is Can efforts to use the Problem Based Learning Model be able to improve the learning outcomes of fourth grade students at SD Negeri Poris Pelawad 6 academic year 2022/2023?Based on the identification of the problem above, the limitation of the problem in this study that can be stated is the ability of students' creativity in developing their thoughts.